Towards quantitative perfusion MRI of the lung in COPD: the problem of short-term repeatability - Ter-Karapetyan, Alvard; Triphan, Simon M. F.; Jobst, Bertram; Anjorin, Angela; Ley-Zaporozhan, Julia; Ley, Sebastian; Sedlaczek, Oliver; Biederer, Jürgen; Kauczor, Hans-Ulrich; Wielpütz, Mark Oliver (PLOS ONE, 2018)
Purpose 4D perfusion magnetic resonance imaging (MRI) with intravenous injection of contrast agent allows for a radiation-free assessment of regional lung function. It is therefore a valuable method to monitor response to treatment in patients with chronic obstructive pulmonary disease (COPD). This study was designed to evaluate its potential for monitoring short-term response to hyperoxia in COPD patients. Materials and methods 19 prospectively enrolled COPD patients (median age 66y) underwent paired dynamic contrast-enhanced 4D perfusion MRI within 35min, first breathing 100% oxygen (injection 1, O2) and then room air (injection 2, RA), which was repeated on two consecutive days (day 1 and 2). Post-processing software was employed to calculate mean transit time (MTT), pulmonary blood volume (PBV) and pulmonary blood flow (PBF), based on the indicator dilution theory, for the automatically segmented whole lung and 12 regions of equal volume. Results Comparing O2 with RA conditions, PBF and PBV were found to be significantly lower at O2, consistently on both days (p<10-8). Comparing day 2 to day 1, MTT was shorter by 0.59±0.63 s (p<10-8), PBF was higher by 22±80 ml/min/100ml (p<3·10-4), and PBV tended to be lower by 0.2±7.2 ml/100ml (p = 0.159) at both, RA and O2, conditions. Conclusion The second injection (RA) yielded higher PBF and PBV, which apparently contradicts the established hypothesis that hyperoxia increases lung perfusion. Quantification of 4D perfusion MRI by current software approaches may thus be limited by residual circulating contrast agent in the short-term and even the next day.
Gesehen am 14.5.2019